(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
The acute hospital setting can be psychologically demanding for medical professionals generally. Working within the medical model, with its focus primarily on the physical, and faced with the patient’s fear and suffering, the clinician’s self-defence can be to hold back from an empathic response, to concentrate upon attending to the patient’s body rather than the mind. To emphasise with the patient’s suffering is often felt on some level by the clinician to be potentially self-destructive. The psychotherapist however, is, by definition, up close to the mind: that is the main focus. So how does one offer existential psychotherapy in an acute hospital setting with patients who are up against their own mortality, and their imminent death, and, moreover who may be in pain and suffering, without it having a destructive impact on the therapist? How does one face up to the physical process of dying – both others’ deaths and one’s own? This paper attempts to open up this question with reference to my own experience working within Palliative Care in the acute setting and with reference to the writings of Georges Bataille and the later work of Heidegger.